P-513 Analysis of the extent of dropout-rates by extraction from cumulative live birth rates in IVF/ICSI: systematic review and meta-analysis. (6th August 2021) - Vereeck, S; Sugihara, A; De Neubourg, D
Abstract: Study question: The purpose of this systematic review is to calculate dropout-rates of IVF/ICSI treatment by analysing the published cumulative live birth rates of IVF/ICSI treatment. Summary answer: One out of three patients stop their treatment after their first IVF/ICSI cycle and dropout-rates tend to increase per consecutive cycle. What is known already: Cumulative live birth rates (CLBRs) have created the possibility to present realistic probabilities of having a live birth after IVF/ICSI treatment. However, it is noted that a significant percentage of the patients stop their treatment before having a child ("dropout"). Possible reasons and predicting factors for dropout of treatment are already extensively investigated. However, only a few studies try to report about the incidence of dropout. Publications on CLBRs of large numbers of patients allow the extraction of dropout-rates. These rates will provide insight in the extent of the problem and could be used as a reference for interventional studies. Study design, size, duration: Four databases (PubMed, The Cochrane Library, EMBASE, DoKS) were systematically searched from 1992 to December 2020. Search terms referred to "cumulative live birth" AND "ART/IVF/ICSI". No restrictions were made on the type or language of publication. Studies were included if they reported absolute numbers of patients and live births per consecutive complete IVF/ICSI cycle or per consecutive embryo transfer cycle, starting from the first IVF/ICSI cycle for each patient. Participants/materials, setting, methods: Dropout-rates per cycle were calculated in two manners: "intrinsic dropout-rate" with all patients that started the particular IVF/ICSI cycle in the denominator, and "potential dropout-rate" with all patients who did not achieve a live birth after IVF/ICSI (and potentially could have started a consecutive cycle) in the denominator. Dropout-rates were analysed for consecutive complete cycles and consecutive embryo transfer cycles, because these two manners are used in reporting CLBRs, often related to the reimbursement policy. Main results and the role of chance: This review included 29 studies and almost 800, 000 patients from different countries and registries. Regarding the patients who started their first IVF/ICSI cycle, trying to conceive their first child by IVF/ICSI, intrinsic dropout-rate was 33% (weighted average) after the first complete cycle, meaning they did not return for their second oocyte retrieval cycle. After the first embryo transfer cycle, intrinsic dropout-rate was 27% (weighted average), meaning those patients did not return for their next frozen-thawed embryo transfer cycle or for the next oocyte retrieval cycle. Regarding the patients who did not achieve a live birth after the first complete cycle, potential dropout-rate was 48% (weighted average), and 37% (weighted average) after the first embryo transfer cycle. Both potential and intrinsic dropout-rates for both consecutive complete and embryo transfer cycles tended to increase with cycle number. One study on second IVF/ICSI conceived children showed a potential dropout-rate after the first complete cycle of 29%. From studies on women >40 years of age, the potential dropout-rate after the first complete cycle was 45% (weighted average) and from studies with the uses of testicular sperm extraction, the potential dropout-rate after the first complete cycle was 34% (weighted average). Limitations, reasons for caution: Our analysis was hampered by the different ways of reporting on CLBRs (complete cycles versus embryo transfer cycles), informative censoring, patients changing clinics and spontaneous pregnancies. Dropout-rates were potentially overestimated given that spontaneous pregnancies were not taken into account. Wider implications of the findings: The extent of dropout in IVF/ICSI treatment is substantial and has an important impact on its effectiveness. Therefore, it is a challenge for fertility centers to try to keep patients longer on board, by taking into account the patients' preferences and managing their expectations. Trial registration number: PROSPERO Registration number: CRD42020223512